2022
DOI: 10.1088/1741-2552/ac9edd
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multiple-stimulus auditory brain–computer interface with semi-supervised learning and prior probability distribution tuning

Abstract: Objective. Auditory brain–computer interfaces (BCIs) enable users to select commands based on the brain activity elicited by auditory stimuli. However,existing auditory BCI paradigms cannot increase the number of available commands without decreasing the selection speed, because each stimulus needs to be presented independently and sequentially under the standard oddball paradigm. To solve this problem, we propose a double-stimulus paradigm that simultaneously presents multiple auditory stimuli. Approach. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Although non-invasive BCI research and development often involve healthy subjects, studies have shown that brain-decoding functionality remains intact in individuals with impairments 39 , and can have positive impacts on those rehabilitating from strokes 40 . However, even with recent innovations, non-invasive BCIs still have online accuracy rates of approximately 70 to 80% 34 , 41 43 , leaving room for improvement before widespread clinical adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Although non-invasive BCI research and development often involve healthy subjects, studies have shown that brain-decoding functionality remains intact in individuals with impairments 39 , and can have positive impacts on those rehabilitating from strokes 40 . However, even with recent innovations, non-invasive BCIs still have online accuracy rates of approximately 70 to 80% 34 , 41 43 , leaving room for improvement before widespread clinical adoption.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, non-invasive BCIs present a more feasible option for widespread application. Non-invasive BCIs have demonstrated ability to move a robotic arm 9,10 , control a wheelchair 11 , or type on a virtual keyboard 12,13 , but even recent innovations in non-invasive BCIs have online accuracy rates of approximately 70 to 80% 9, [14][15][16] , which leave room for improvement before seeking widespread clinical use.…”
Section: Introductionmentioning
confidence: 99%